Tax Compliance Base on Knowledge at the Bekasi City KPP Madya in Efforts to Support State Revenue Security - Sumarno Manrejo; Tutty Nuryati (Management Research Studies Journal, 2023)
Purpose: Testing influence mandatory knowledge relationship tax with mediation intention pay tax to obedience tax in effort support security Indonesian state revenue at KPP Madya Bekasi Kota.Design/ Methodology/Approach: Unit of analysis is Must Taxes that have report notification letter Annual 202 2 . Primary data in the form questionnaire with Likert scale 1-5. Data is processed  use Lisrel 8.80. Approach study is explanative quantitative research with measurement indicator reflective . Validity test whole  variable own valid and reliable predicate . The average value of the loading factor by whole variable latency used is valid as measure compliance with tax variables, Findings: Intention must tax as variable knowledge mediation must tax influential positive significant to obedience tax . Implications Practical: Required  inspection must tax Good must corporate tax and must personal tax in order to test implementation self assessment system in Indonesia in effort increase obedience tax Originality/value: Deliver contribution to Service Office Bekasi City Middle Tax that knowledge must tax with mediation intention pay tax can influence obedience tax inside effort help security Indonesian state revenue .